2009
DOI: 10.1039/b811829a
|View full text |Cite
|
Sign up to set email alerts
|

A direct method for the preparation of glycolipid–metal nanoparticle conjugates: sophorolipids as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles and their antibacterial activity

Abstract: The production of a new class of glycolipid-metal nanoparticle conjugates, namely, sophorolipid reduced/capped silver nanoparticles is demonstrated for the first time, by unveiling the reducing and capping abilities of sophorolipid derived from oleic acid. It is also demonstrated that the sophorolipid capped Ag nanoparticles are highly potent antibacterial agents, against both Gram-positive and Gram-negative bacteria. The utilization of sophorolipid brings out several advantages, such as eliminating the necess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
78
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(80 citation statements)
references
References 78 publications
2
78
0
Order By: Relevance
“…Capping agents are essential for preventing nanoparticle aggregation and increasing solubility of the nanosystem, and they can also be used as a site for bioconjugation of the nanoparticle with important molecules. 12,13 Stabilization of nanoparticles can be achieved by adding capping agents, which bind to the nanoparticle surface via covalent bonds or chemical interactions. 14 Thus, biologically prepared nanomaterials are extremely valuable because nanoparticles can be coated with a lipid or protein layer that confers physiological solubility and stability, which are critical parameters for biomedical applications that are currently a challenge for other synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Capping agents are essential for preventing nanoparticle aggregation and increasing solubility of the nanosystem, and they can also be used as a site for bioconjugation of the nanoparticle with important molecules. 12,13 Stabilization of nanoparticles can be achieved by adding capping agents, which bind to the nanoparticle surface via covalent bonds or chemical interactions. 14 Thus, biologically prepared nanomaterials are extremely valuable because nanoparticles can be coated with a lipid or protein layer that confers physiological solubility and stability, which are critical parameters for biomedical applications that are currently a challenge for other synthesis methods.…”
Section: Introductionmentioning
confidence: 99%
“…Sophorolipids were also tested for use in nanoparticles synthesis and reported to be good reducing and capping agents for cobalt and silver particles (Kasture et al, 2007, as cited in Van Bogaert & Soetaert, 2010. Singh et al, (2009) demonstrated the antibacterial activity of sophorolipid-coated silver and gold nanoparticles against both Gram-positive and -negative bacteria. They also verified that sophorolipid-coated gold nanoparticles were more cyto and geno-compatible with respect to silver nanoparticles (Singh et al, 2010).…”
Section: Nanoparticlesmentioning
confidence: 98%
“…31,32 Usually, in such methods, stabilization of NPs is carried out via additional capping agents, such as water-soluble polymers, oligosaccharides, polysaccharides, sodium dodecyl sulfate, cyclodextrin, and so on. 30,33 However, such chemical methods imply toxic chemicals, hazardous conditions, and costly apparatus in comparison to the green synthesis of silver NPs involving biocompatible ingredients under the physiological conditions of temperature and pressure. Moreover, the biologically active molecules involved in the synthesis of NPs, especially phytomolecules, that are present in the plant extract (PE) often act as functionalizing ligands, thereby limiting the use of any external capping agents.…”
Section: Introductionmentioning
confidence: 99%